Народные русские сказки А. Н. Афанасьева: в 5 т. (А. Н. Афанасьев) - Афанасьев Александр Николаевич (1992)
Экземпляры: КХ (20110823) / Инвентарный номер: 1010689 / Цена: 80.00 / Сис.шифр: 82.3(2) / Авт.знак: А 94 / ГРНТИ: 17 / ББК: 82.3(2=411.2)-442.06